Рушник: мистецтво і промисел - Китова, С. (Народна творчість та етнографія, 2005)
The applied folklore by its nature is the most ancient form of the human art work. First primitive ornaments on the dishes, clothing, tell us about the attempt of the people to feel the esthetic laws of the things. The esthetic values of our ancestors were developing in the tight connections with the nature itself which was reflected in the art. This article pays a special attention to the symbolism of the ornaments of the Ukrainian traditional folk towel called rushnyk n the context of the understanding of more deep problems connected to this kind of folk art. Author is analyzing the ornament as a reflection of complex of psychological processes which occur in folk's mind under the influence of certain circumstances. Embroidery it's a women's art and the colors and ornaments of Ukrainian ryshnyky show an attempt of Ukrainian women who made them to create another reality, the reality of cozy safe home which was not always the case in real life. The author considers rushnyk to be more of a craft then an art and tries to prove it through the analyses of the symbols and functions of this kind of craft.